Is merino wool disappearing in Portugal: Merino Beira Baixa case - Rodrigues, J.P.V. (2013)
In Portugal we are facing a fast decrease in the production of good quality wool. This situation can be seen from a qualitative and quantitative point of view by looking at the most extreme situation, which involves almost the extinction of a Merino breed - Merino Beira Baixa (MBB)- due to its inability to produce high milk quantities when subjected to the better hadling of the more intensive production systems. The changes in the production systems and the need for higher milk production for the production of PDD cheese (Protected Designation of Origin - EEC Regulation 2081/92), but without indexation to the milk of the MBB sheep breed (as opposite to other cheeses made exclusively with milk from one specific breed), has led to the massive introduction of extotic sheep breeds specialising in milk production. In the last decade, the MBB animals have decreased by more than 90%, and urgent actions is needed to prevent the disappearance of one more indigenous breed.